Multicenter Phase II Study of Tivozanib (AV‐951) and Everolimus (RAD001) for Patients With Refractory, Metastatic Colorectal Cancer. (11th April 2014) - Wolpin, Brian M.; Ng, Kimmie; Zhu, Andrew X.; Abrams, Thomas; Enzinger, Peter C.; McCleary, Nadine J.; Schrag, Deborah; Kwak, Eunice L.; Allen, Jill N.; Bhargava, Pankaj; Chan, Jennifer A.; Goessling, Wolfram; et al.
Abstract : Background: Treatments that target the vascular endothelial growth factor (VEGF) pathway have efficacy in colorectal cancer. We evaluated tolerability and efficacy of tivozanib (an oral VEGF receptor‐1, ‐2, ‐3 inhibitor) plus everolimus (an oral mammalian target of rapamycin inhibitor). Methods: The phase Ib study followed a 3 + 3 dose‐escalation design with three dose levels. The primary objective in the follow‐on phase II study was improvement in 2‐month progression‐free survival (PFS) from 30% (historical benchmark) to 50% in patients with refractory, metastatic colorectal cancer. Results: Dose‐limiting toxicities in the phase Ib study were grade 3 fatigue and dehydration. Oral tivozanib (1 mg daily for 3 of 4 weeks) and oral everolimus (10 mg daily continuously) were advanced to a 40‐patient phase II study. The most common grade 3–4 adverse events were thrombocytopenia and hypophosphatemia. The 2‐month PFS rate was 50%, with 20 of 40 patients having stable disease (SD). Seven (18%) patients were treated for ≥6 months. Median PFS and overall survival (OS) times were 3.0 months (95% confidence interval [CI]: 1.9–3.6 months) and 5.6 months (95% CI: 4.4–10.6 months), respectively. Patients who developed grade 1+ hypertension had increased SD rates (65.2% vs. 29.4%) and longer OS times (10.6 vs. 3.7 months). Conclusions: The oral combination of tivozanib and everolimus was well tolerated, with stable disease achieved in 50% of patients with refractory, metastatic colorectal cancer. Abstract : 摘要 背景 以血管内皮生长因子 (VEGF)通路为靶点的药物可有效治疗结直肠癌。我们评估了 Tivozanib（一种口服的 VEGF 受体 1、2、3 抑制剂）与依维莫司（一种口服的哺乳动物类雷帕霉素靶蛋白抑制剂）联合用药的耐受性和疗效。 方法 Ib 期研究评估了三个剂量水平下的 3 + 3 剂量递增方案。后续 II期研究的主要目标是，将难治性转移性结直肠癌患者的 2 月无进展生存率 (PFS) 从 30%（历史基准水平）提高至 50%。 结果 Ib 期研究中的剂量限制性毒性为 3级疲乏和脱水。II 期研究让 40 名患者联合服用 Tivozanib（1 mg/天，给药 3 周，每 4 周一疗程）和依维莫司（10 mg/天，持续给药）。最常见的 3∼4 级不良事件包括血小板减少症和低磷血症。受试者的 2 月 PFS 为 50%，其中 40 名受试者中有 20 名达到了病情稳定 (SD)。有 7 名 (18%) 患者接受了 ≥ 6个月的治疗。中位 PFS 和总生存期(OS)分别为 3.0个月 [95% 置信区间（CI ）： 1.9∼3.6 个月]和 5.6 个月（95% CI： 4.4∼10.6 个月）。出现 1 + 级高血压的患者具有更高的 SD 率 (65.2% 相比 29.4%)和更长的 OS 期（10.6 相比 3.7 个月）。 结论 Tivozanib 与依维莫司的联合使用不仅耐受良好，而且使 50%的难治性转移性结直肠癌患者达到了病情稳定。